STRATEGI PENANGANAN SOAL UKBI MENURUT DIMENSI SOAL FAKTUAL [Strategies of UKBI Question Management Based on Dimension of Factual Question] - Nanik Sumarsih (TOTOBUANG, 2018)
This study discussed about the  skill level of junior and senior high school teachers at Yogyakarta in answering the factually UKBI and  handled question strategy according to  factual question dimension.This research used descriptive quantitative approach.The research aimed to determine the good or poor language-level of the educators  which had been measured by UKBI. Therefore, the result of this study wa  originally presented by considering its productivity.The research  followed several steps, they were: (1) collecting and classifying of data, (2) analysing data, (3) presenting analysis result.The ability of junior and senior high school teachers at DIY in answeingr factual question was  81%. Based on the character of factual question,the strategy that should be used was that  applying 5W 1H strategy (who, what, where, when, why, and how)_. This strategy can be described as follows: Who is asking about a person as doer. What is asking about an event that happens. Where is asking about where an event takes place. When is asking time when an event happens. Why is asking about reason why it happens. How is asking how an event happens.Kajian ini membahas tingkat kemahiran guru SLTP dan SLTA di Yogyakarta dalam menjawab soal UKBI yang bersifat faktual beserta strategi penanganan soal menurut dimensi soal faktual. Penelitian ini menggunakan pendekatan kuantitatif deskriptif. Hal ini dimaksudkan untuk menentukan baik buruk kemampuan berbahasa pendidik yang diukur berdasarkan UKBI. Oleh karena itu, hasil penelitian ini memaparkan apa adanya dengan mempertimbangkan produktivitasnya. Langkah penelitian mengikuti tahapan sebagai berikut. Pertama, pencarian dan klasifikasi data. Kedua, analisis data. Ketiga, penyampaian hasil analisis. Kemampuan  guru SLTP dan SLTA di DIY dalam menjawab soal yang bersifat faktual masing-masing adalah 81%. Berdasarkan sifat soal faktual, strategi yang dapat digunakan untuk menjawab bentuk penyoalan ini adalah  5W 1H (who, what, where, when, why, dan how)_ Strategi ini dapat dijabarkan sebagai berikut. Who ialah tentang siapa? What, apa yang terjadi? Where, di mana peristiwa itu terjadi, when, kapan hal itu terjadi? Why, mengapa hal itu terjadi? How, bagaimana hal itu terjadi?